Late-Quaternary history of the alpine flora of the New Hampshire White Mountains - Miller, Norton; Spear, Ray (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1999)
Abstract A distinctive flora of 73 species of vascular plants and numerous bryophytes occurs in the ca. 20 km 2 of alpine tundra in the White Mountains, New Hampshire. The late- Quaternary distribution of these plants, many of which are disjuncts, was investigated by studies of pollen and plant macrofossils from lower Lakes of the Clouds (1 542 m) in the alpine zone of Mount Washington. Results were compared with pollen and macrofossils from lowland late-glacial deposits in western New England. Lowland paleofloras contained fossils of 43 species of vascular plants, 13 of which occur in the contemporary alpine flora of the White Mountains. A majority of species in the paleoflora has geographic affinities to Labrador, northern Québec, and Greenland, a pattern also apparent for mosses in the lowland deposits. The first macrofossils in lower Lakes of the Clouds were arctic-alpine mosses of acid soils. Although open-ground mosses and vascular plants continued to occur throughout the Holocene, indicating that alpine tundra persisted, fossils of a low-elevation moss Hylocomiastrum umbratum are evidence that forest (perhaps as krummholz) covered a greater area near the basin from 7 500 to 3 500 yBP. No calcicolous plants were recovered from sediments at lower Lakes of the Clouds. Climatic constraints on the alpine flora during the Younger Dryas oscillation and perhaps during other cold-climate events and intervening periods of higher temperature may have led to the loss of plant species in the White Mountain alpine zone. Late-glacial floras of lowland western New England were much richer than floras of areas above treeline during late-glacial time and at the present.